The MILP Model for Locating the Temporary Disaster Emergency Operation Centers in Manado Indonesia - Andre Ch. Lasut; Prudensy Febreine Opit; Ronaldo Rottie (Jurnal Teknik Industri, 2020)
The research proposes the Mixed Integer Linear Programming Model (MILP). This model integrates the location decisions and the number of temporary Emergency Operations Center (EOC) to be constructed. This model also focuses on events related to natural disasters, particularly floods. The researchers applied this model according to the flood scenario in five flood-prone districts in Manado, Indonesia. This research focused on maximizing the number of temporary constructed EOCs to provide the relief demands of disaster areas by considering multiple periods. The available budgets were considered as the limited constraints in this model. Therefore, the results showed that the percentage of relief demand satisfaction ranges from 28% to 100%; meanwhile, the number of the to-be-constructed temporary EOCs ranges from 0-3 for each scenario.